Comparison of Maize Silage-based Diets for Dairy Cows Containing Extruded Rapeseed Cake or Extruded Full-fat Soybean as Major Protein Sources - Jiří Třináctý; Michal Richter; Ludmila Křížová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2016)
The trial was carried out on four Holstein cows with initial milk yield of 27.3 ± 1.7 kg.day−1. Cows were divided into two groups – the first was fed a diet based on extruded rapeseed cake (D-ERC), the second one was fed a diet based on extruded full-fat soybean (D-EFFS), both diets contained maize silage and meadow hay. The experiment was divided into 4 periods of 42 days. Intake of dry matter, crude protein and NEL was not affected by the treatment (P > 0.05) while the intake of PDIA, PDIN and PDIE was lower in D-ERC than in D-EFFS (P < 0.05). Milk yield in D-ERC (22.6 kg.d−1) was lower than in D-EFFS (24.7 kg.d−1, P < 0.001) while concentration of milk fat and protein were reverse (P < 0.05). Smaller portion of essential AADI in crude protein intake (CPI) in D-ERC resulted in lower efficiency of CPI utilization for milk protein synthesis in comparison to D-EFFS being 313 and 327 g.kg−1, respectively (P < 0.01). Concentration of AA in blood plasma was not affected by the type of diet except of His and Ile that were higher in D-EFFS (P < 0.01).